Coaction of Wind and Rain Effects on Large-Span Hyperbolic Roofs - Fangjin Sun; Zhonghao Xu; Daming Zhang; Yanlu Wang (Shock and Vibration)
Rainfall is often accompanied by strong winds. The large-span roof structure has a low height, its surrounding turbulence is high, and the wind speed changes greatly. The effects of coaction of wind and rain on the roofs cannot be ignored. Wind-driven rain (WDR) is an oblique movement phenomenon of raindrops generated by wind flow. Four types of hyperbolic roofs, that is, square, rectangular, circular, and elliptical, are selected as the objective to study the wind-driven rain by CFD simulation. Effects of wind direction, wind speed, and rainfall intensity on the WDR are analyzed. Pressure distribution of four types of hyperbolic roofs under coaction of wind and rain is obtained. The results are compared with those from the wind action only. The roofs are partitioned to obtain the coaction of wind and rain pressure of the four large-span hyperbolic roofs with different shapes under the most unfavorable working conditions. The results show that the average pressure coefficient of the roof surface increases with the increase of wind speed and rainfall intensity. The reference value of the average pressure coefficient of wind-driven rain on the surface of the roof is given, which provides a reference basis for the design of wind-driven rain on similar hyperbolic roofs.